Malignant Gastrointestinal Neuroectodermal Tumor (GNET) with Prolonged Disease-Free Survival after Platinum-Based Chemotherapy - Daulath Singh; Mohammed K. Atieh; Mark A. Russell; Muaiad Kittaneh (Case Reports in Oncological Medicine)
Malignant gastrointestinal neuroectodermal tumor (GNET) is a rare disease with a handful of cases described in literature. GNET has only become a well-known/widely accepted entity in the recent years, but it is still not listed in the database of rare diseases. Due to the rarity of disease, there are no guidelines on standard therapeutic approaches in the adjuvant or metastatic setting. Here, we describe a unique case of GNET with a 7-year disease-free survival following adjuvant cisplatin and etoposide chemotherapy. This is the longest disease-free survival that has ever been described in literature and may support using this combination in a larger cohort of patients in the context of a global clinical trial. We will also review the histopathologic features of GNET and potential therapeutic options in the metastatic setting.